A segurança jurídica no novo código comercial: análise dos contratos de integração avícola - Perin, Fernando Luiz (2016)
The objective of this work is to analyze the contractual relationship in poultry farming under the regulation of the project to the new commercial code, which will create specific rules for the relationship between legal and physical agribusiness, through better regulation of contracts. This sector lacks attention due to the absence of legal regulation, on the other hand it is one of the greatest sources of wealth for the country's economy, therefore it should have a better regulation. The work pointed out that, from the perspective of the literature consulted, as well as from the perspective of the interviewees, the project of the new commercial code must have a modernization designation of all the agribusiness sectors, needing to discuss the matter at the national level to avoid damages to the small producers, guaranteeing greater compliance in contracts that until then have been processed customarily, Increasing legal certainty for all parties involved, encouraging greater investment and decreasing legal demands and their costs.